Assessment of the Feelings and Attitudes of Children towards Their Dentist and Their Association with Oral Health. (26th March 2014) - Patır Münevveroğlu, Aslı; Ballı Akgöl, Beyza; Erol, Tuğba
Abstract : This study assessed the feelings and attitudes of children toward their dentists and their association with oral health. Methods. A questionnaire designed to evaluate the attitudes of children toward dentists and preferences was completed by 200 children and their families. In addition, the children were examined and the World Health Organization (WHO) method was used to obtain dmft and DMFT scores. Results. The mean dmft and DMFT scores were 3.52 ± 2.44 and 1.35 ± 1.29, respectively. Of the children, 92.5% reported that they had visited a dentist before. Of the children who had visited dentists, approximately 71.5% reported that they enjoyed their visits. Of the children, 84% preferred female dentists, 76.5% preferred dentists that wore a colored coat, and 63% preferred a decorated dental clinic over a plain clinic. The mean dmft and DMFT values of children who were afraid of dentists were significantly higher than those of children who were not (P < 0.01 and P < 0.05, resp.). Conclusion. Children have strong perceptions and preferences regarding the appearance of their dentists and dental clinics. The results of this study might help dentists to improve their delivery of care.